2013
DOI: 10.1002/jcb.24528
|View full text |Cite
|
Sign up to set email alerts
|

Control of Fiat (factor inhibiting ATF4‐mediated transcription) expression by Sp family transcription factors in osteoblasts

Abstract: FIAT (factor inhibiting ATF4-mediated transcription) represses Osteocalcin gene transcription and inhibits osteoblast activity by heterodimerizing with ATF4 to prevent it from binding DNA. It thus appears important to identify and characterize the molecular mechanisms that control Fiat gene expression in osteoblasts. In silico sequence analysis identified a canonical GC-box within a 1,400 bp region of the proximal Fiat gene promoter. Electrophoretic mobility shift assays (EMSA) with MC3T3-E1 osteoblastic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The decreased inhibition of IKZF1 on EPAS1-C/insertion/T promoter as compared with that on EPAS1-C/deletion/C promoter ( Figure 2A ) might be caused by the steric hindrance of other transcriptional factors binding to the 40-bp insertion fragment. Sp1 is a zinc finger transcription factor that binds to GC-rich motifs of many promoters acting as an activator 32 or a repressor 33 , which is involved in many cellular processes, including cell differentiation, cell growth, apoptosis 34 , immune responses 35 and so on. Sp1 contains three spliced transcript variants encoding different isoforms (isoform 1–3).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased inhibition of IKZF1 on EPAS1-C/insertion/T promoter as compared with that on EPAS1-C/deletion/C promoter ( Figure 2A ) might be caused by the steric hindrance of other transcriptional factors binding to the 40-bp insertion fragment. Sp1 is a zinc finger transcription factor that binds to GC-rich motifs of many promoters acting as an activator 32 or a repressor 33 , which is involved in many cellular processes, including cell differentiation, cell growth, apoptosis 34 , immune responses 35 and so on. Sp1 contains three spliced transcript variants encoding different isoforms (isoform 1–3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on similarities with other SP family members, SP7 was first thought to bind GC-rich sequences 1 , 9 11 which are present in the promoters of many genes important for osteoblast functions 12 , 13 , such as Col1a1 and Col1a2 14 . However, other studies have shown evidence for a lack of binding preference for a GC-rich sequence 15 . More recently, Hojo et al showed that SP7 differs from other SP proteins in that it has a lower binding affinity for GC-rich sequences, and instead interacts with DLX5 and with AT-rich promoter/enhancer sequences to transactivate genes in osteoblasts 16 .…”
Section: Introductionmentioning
confidence: 94%
“… 92 , 94 , 95 Factors inhibiting ATF4-mediated transcription (Fiat) have been found to suppress ATF4 activity and, co-expressed in osteoblasts 96 , 97 and modulated by the Sp family, to exclude Osx. 98 In the matrix mineralization stage, ATF4 is positively regulated, to a large extent, by c-Jun N-terminal kinase (JNK), affecting the expression of OCN and BSP. 99 Moreover, ATF4 can also bind to the promoter of RANKL and can ultimately inhibit bone resorption.…”
Section: Mirnas In Osteoblast Lineage and Bone Formationmentioning
confidence: 99%